To enhance employability in higher education - a real connection to labour market - Marques dos Santos, Paula (2016)
School of Technology and Management of Lamego develops since 2009 a project to reinforce its connections to the real needs of labour market. in this way, we developed until now three areas: multidisciplinarity volunteering work teams, collaborative training of students and the cooperation with several organizations to improve their sutainability through strategic methodologies.with those methodologies we tried to improve our students' employability, as well as to dialogue permanently with companies and other organizations to understand what they need from their human resources to be more competitive. wuth this article we intend to present the results accomplished until now and to present the project for the next e years, as well as to find out other higher education institutions of different regions or coutries that are interested in this project.